Translocation of enzymes into a mesoporous MOF for enhanced catalytic activity under extreme conditions. Issue 14 (13th March 2019) - Navarro-Sánchez, José; Almora-Barrios, Neyvis; Lerma-Berlanga, Belén; Ruiz-Pernía, J. Javier; Lorenz-Fonfria, Victor A.; Tuñón, Iñaki; Martí-Gastaldo, Carlos
Abstract : Translocation of protease into mesoporous MIL-101-NH2 results in enhanced catalytic activity, excellent recyclability and tolerance to competing enzymes. Abstract : Enzymatic catalysis is of great importance to the chemical industry. However, we are still scratching the surface of the potential of biocatalysis due to the limited operating range of enzymes in harsh environments or their low recyclability. The role of Metal–Organic Frameworks (MOFs) as active supports to help overcome these limitations, mainly by immobilization and stabilization of enzymes, is rapidly expanding. Here we make use of mild heating and a non-polar medium during incubation to induce the translocation of a small enzyme like protease in the mesoporous MOF MIL-101(Al)-NH2 . Our proteolytic tests demonstrate that protease@MIL-101(Al)-NH2 displays higher activity than the free enzyme under all the conditions explored and, more importantly, its usability can be extended to extreme conditions of pH and high temperatures. MOF immobilization is also effective in providing the biocomposite with long-term stability, recyclability and excellent compatibility with competing enzymes. This simple, one-step infiltration strategy might accelerate the discovery of new MOF-enzyme biocatalysts that meet the requirements for biotechnological applications.